Entre el deseo y la realidad: aproximación al incesto en la comedia áurea - Sáez García, Adrián J. (El Colegio de México, 2013)
The attractive of the incest as a literary theme has favored its appearancein different texts. In the theater of the Golden Age, the incestcould appear according to four modalities, founded in the criteriaof culmination of the act and the relatives implicated in it (incestbetween parents and children or between brothers and sisters; in verticalor horizontal direction). This article explores some of the characteristicsof the dramatic representation of incest: the conflict betweenlove and desire, and the force of blood which advices of the real kinship(in relation with the edipical echoes), the occasional connectionwith religion or politics, the differences established by the concept ofdecorum, among other questions.